The static and dynamic stiffness behaviour of composite golf shafts and their constituent materials - Betzler, N. F.; Slater, C.; Strangwood, M.; Monk, S. A.; Otto, S. R.; Wallace, E. S. (Sports Engineering, 2011)
Golf shafts are normally characterised using static or quasi-static tests, yet the golf swing itself is dynamic. The purpose of this research was to determine whether stiffness properties obtained from these tests can be used when modelling the dynamic behaviour of golf shafts made from carbon fibre reinforced polymer (CFRP). Three shafts, matched for all properties except shaft flex, were subjected to human swing testing by 12 skillful players whilst strains were recorded. Peak principal strains as well as strain rates increased as shaft flex decreased (p < 0.001). CFRP flat panels with lay-ups similar to those contained in the shafts were constructed and tested statically and at strain rates between 10-4 and 4 s-1. Some level of strain-rate dependency was found for these panels, but only for strain rates exceeding those seen during a swing, which suggests that static material tests are appropriate for measuring the dynamic stiffness of golf shafts.